Titik Temu Islam dan Demokrasi : Analisis Sistem Pemilihan Umum Presiden di Turki dan Indonesia - Al djufri, Helmy; Alfaridah, Dini Inasyah (SIYASI: Jurnal Trias Politica, 2023)
Democracy is a system that exists in various countries with a government where supreme power lies in the hands of the people. However, in reality the implementation of democracy is difficult to implement ideally in accordance with the values contained in democracy itself, and how democracy is implemented in Islamic democracy, especially if the election systems between Turkey and Indonesia are clearly different or have similarities between the two. One thing that often happens regarding the implementation of democratic government is presidential elections, so that we can compare Islam and democracy in these two countries. This research uses normative juridical research methods obtained from library data and statutory regulations. The results of this research show that firstly, the Presidential General Election in Indonesia and Turkey are clearly stated in the Constitution, both the Constitution of the Republic of Turkey and the 1945 Constitution in Indonesia, as for the mechanism for the direct Presidential General Election System, it is regulated in article 2 of Law Number 7 2017 regarding the Presidential General Election. Meanwhile. The two similarities are related to the system for holding the Presidential General Election, namely using a direct election system and regarding the comparison of the Presidential Elections of the Republic of Indonesia and Turkey, there are many Similarities were found, such as the presidential election system in both countries using a direct election system, presidential candidates having to be nominated by a party, the party system using a multiparty system, the existence of a party threshold for nominating the president and office of President in Indonesia an Turkey which is 5 (five) years for a period and can be nominate for two more periods. Meanwhile, the difference between the general elections of the Republic of Indonesia and Turkey is that there is a minimum age limit for the president and a threshold percentage for the party.